Audit Opinion And Sharia Compliance In Increasing Trust In Zakat Baznas Padang Panjang - Nasfi Nasfi; Zakaria Aziz; Yunimar Yunimar; Adi Perwira (Institut Agama Islam Sumatera Barat, 2024)
The purpose of this research is to determine audit opinion and sharia compliance in increasing trust in zakat in Baznas Padang Panjang City. Type of qualitative research, phenomenological approach method. Baznas Research Location Padang Panjang City. The results of research on audit opinion and sharia compliance are complementary audit instruments. Sharia compliance audits complement conventional financial audits, so that the picture of Baznas' financial performance reports is more comprehensive. So that Baznas is worthy of being an authority institution in carrying out zakat management professionally and with integrity in zakat management, realizing a commitment to transparency, increasing the value of accountability as a manager of zakat funds and finally building a positive reputation and image in society. Public trust is the main factor in increasing zakat receipts at Baznas. A positive audit opinion and sharia compliance predicate is a combination of instruments that contribute to increasing Baznas zakat receipts. The research is implemented in providing recommendations to zakat management institutions that have not carried out audit activities to start implementing them. Audits help zakat institutions in building public recognition and trust.